2016
DOI: 10.1186/s12906-016-1508-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hippocampal MEK1 contributes to the cumulative antinociceptive effect of electroacupuncture in neuropathic pain rats

Abstract: BackgroundElectroacupuncture (EA) intervention can relieve a variety of pain; however, optimal EA protocols have not been clearly determined. In addition, although central mitogen-activated protein kinase kinase (MEK) signaling has been shown to be involved in the antinociceptive effect of acupuncture stimulation, its characteristics at different time-points of EA intervention have not been fully elucidated. Therefore, the present study investigated the relationship between the effects of different numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…The up-down method was used to assess the mechanical sensitivity, which was described previously. 17 , 19 , 20 Briefly, the von Frey filament with logarithmically incremental stiffness was used to measure the paw withdrawal thresholds, 0.04–2.04 g (0.04, 0.07, 0.16, 0.4, 0.60, 1.0, 1.4, 2.04 g); the mid-value of the series was 0.4 g, which was applied first. The animals were firstly adapted for 1 week in the test room, then, the corresponding stimulation method was evaluated in advance for 30 minutes before the formal testing.…”
Section: Methodsmentioning
confidence: 99%
“…The up-down method was used to assess the mechanical sensitivity, which was described previously. 17 , 19 , 20 Briefly, the von Frey filament with logarithmically incremental stiffness was used to measure the paw withdrawal thresholds, 0.04–2.04 g (0.04, 0.07, 0.16, 0.4, 0.60, 1.0, 1.4, 2.04 g); the mid-value of the series was 0.4 g, which was applied first. The animals were firstly adapted for 1 week in the test room, then, the corresponding stimulation method was evaluated in advance for 30 minutes before the formal testing.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic pain is a multidimensional experience that continually affects the sensory, motor, emotional, cognitive, and other functions. [25][26][27] Neuropathic pain following BPAI is one of the most intractable types of chronic pain. [28][29][30][31] Studies have demonstrated that abnormal brain activity is an important aspect of its occurrence/persistence and might be associated with its severity.…”
Section: Discussionmentioning
confidence: 99%
“…38 The expression of pMEK1 in the hypothalamus was gradually down-regulated following continuous intervention of 2/15Hz EA and the effect was time dependent and cumulative. 42 In the behavioural assessment, MWT was used to detect mechanical allodynia, which has been frequently used in the sensation tests following brachial plexus nerve, median, and ulnar nerves, and sciatic nerve injuries in previous studies. [43][44][45][46] BPAI-induced pain in the injured forelimb subsequently caused central sensitisation and facilitation of pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, many studies focused on effects and underlying mechanisms of acupuncture through animal experiments, offering scientific evidences and theoretical support to using acupuncture treatment clinically [ 7 , 14 , 40 ]. Most of them were undergone in the field of somatic pain because of the existence of mature animal models [ 12 , 16 , 20 , 21 , 23 , 33 , 34 ]. For examples, reports showed that acupuncture can alleviate inflammatory pain under the skin and its surrounding tissues [ 20 , 21 , 23 ], joint pain [ 33 , 34 ] and some neuropathic pain in the animal’s limbs [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%